2019
DOI: 10.1128/aac.00338-19
|View full text |Cite
|
Sign up to set email alerts
|

Tridecaptin M, a New Variant Discovered in Mud Bacterium, Shows Activity against Colistin- and Extremely Drug-Resistant Enterobacteriaceae

Abstract: The World Health Organization has categorized the Gram-negative superbugs, which are inherently impervious to many antibiotics, as critical priority pathogens due to the lack of effective treatments. The breach in our last-resort antibiotic (i.e., colistin) by extensively drug-resistant and pan-drug-resistant Enterobacteriaceae strains demands the immediate development of new therapies. In the present study, we report the discovery of tridecaptin M, a new addition to the family, and its potential against colis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 64 publications
2
36
0
Order By: Relevance
“…Secondly, rampant overuse of antibiotics has yielded, and still is yielding new antibiotic-resistant strains that cannot be killed by known antibiotics (Neville and Jia, 2019). Thirdly, development of new antibiotics is stalling (N'Guessan et al, 2018;Jangra et al, 2019), because their effective lifetime before the first resistant strains arise, is becoming shorter and shorter, decreasing the incentive for commercialization and therewith clinical use of new antibiotics (Liu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, rampant overuse of antibiotics has yielded, and still is yielding new antibiotic-resistant strains that cannot be killed by known antibiotics (Neville and Jia, 2019). Thirdly, development of new antibiotics is stalling (N'Guessan et al, 2018;Jangra et al, 2019), because their effective lifetime before the first resistant strains arise, is becoming shorter and shorter, decreasing the incentive for commercialization and therewith clinical use of new antibiotics (Liu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, they exhibit activity against some antibiotics-resistant bacterial species. For instance, the tridecaptin M was found to exhibit activity against many colistin-resistant E. coli strains in vitro and in vivo [15]. Importantly, a number of studies have shown that AMPs plays a critical role in immune regulation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Tridecaptins are a class of lipopeptide antibiotics that retain activity against multidrug-resistant Gram-negative bacteria. The main members of this class include tridecaptin A [ 35 ], tridecaptin B [ 36 ], and tridecaptin M [ 37 ]. Recently, unacylated tridecaptin A 1 (without the lipid moiety; Figure 1 ), though ineffective itself, was reported to potentiate (or reduce the minimum inhibitory concentration of) Gram-positive antibiotics in Gram-negative bacteria including Enterobacteriaceae and A. baumannii [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, unacylated tridecaptin A 1 (without the lipid moiety; Figure 1 ), though ineffective itself, was reported to potentiate (or reduce the minimum inhibitory concentration of) Gram-positive antibiotics in Gram-negative bacteria including Enterobacteriaceae and A. baumannii [ 38 ]. Tridecaptins have very low intrinsic activity against A. baumannii [ 36 , 37 ], but they could still permeabilize the outer membrane very efficiently [ 39 ]. The naturally occurring tridecaptins are active against Enterobacteriaceae but have not been investigated for their potential in combination therapy.…”
Section: Introductionmentioning
confidence: 99%